Analysis of Creative Product Potentials of Pandawa Beach, Kutuh Village, Bali - A. Agung Putu Swabawa; I Dewa Gede Ari Pemayun; Luh Linna Sagitarini (Soshum: Jurnal Sosial dan Humaniora, 2018)
This research was conducted in coastal tourist area of ​​Pandawa village of Kutuh, sub-district of south Kuta Badung. The goal is to identify the potential of Pandawa beach area, formulate creative tourism product, and to know the perception of tourists toward the natural conditions of Pendawa beach, the socio-cultural conditions, and the condition of tourism infrastructure at Pandawa. Data collection was done by using survey method, questionnaire, interview, documentation, focused group discussion, and literature study. Analytical tool used to analyse data is quantitative analysis in the form of descriptive statistic with the help of Likert scale, and using qualitative analysis technique in the form of descriptive analysis. The analysis shows that there are five identifiable natural potentials at Pandawa beach namely the towering limestone cliffs, white sandy beaches, seaweed, clear blue sea, and Coral Garden. From the socio-cultural aspect, include: traditional dance and dance performances in the form of Ramayana Ballet, cremation ceremony, communal cooperative system, temple and statue of Dewi Kunti and Panca Pandawa on the cliff along the road to Pandawa beach. Creative tourism products that can be formulated on the beach Pandawa, namely in the form of: maritime museum and seaweed cultivation and culinary. The perception of tourists to the natural conditions of Pandawa beaches, socio-cultural, infrastructure, and the existence of tourism facilities are good category, with an average score of 3.07 (foreign) and 2.90 (domestic). Of the four components of tourism products assessed, the best value is the condition of the natural environment with a score of 3.23 (domestic tourists) and 3.19 (foreign tourists), while the lowest score is the existing tourism facilities in Pantai Pandawa with a score of 2 , 97 (domestic tourists), while for foreign tourists the lowest score is public infrastructure with a score of 2.30 including less category.